Between Lome and Maastricht : the strategy of ECDPM 1994-1996 (ECDPM MaastrichtNL, 1994)
Provides a redefinition of the Centre's aim, objectives and guiding principles for programme development. Identifies the partners with whom the Centre works. Explores the consequences of securing a financial base and of putting together a set of programmes based on perceived needs in ACP countries and linked to demonstrated competence in the Centre.
DC